Body Constitution, grip stregth, and Vital Capacity of Children 15 to 18 Years in Samigaluh Highland and Galur Lowland Kulonprogo Yogyakarta - Janatin Hastuti Janatin Hastuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: Growth of children at age of 15 to 18 years old has an important influence on providing body constitution in their adult. Grip strength and vital capacity express functional effort of organs or parts of the body. Therefore, it certainly relates to the shape and size of the body or the body constitution. Different environment in highland and lowland affects the body constitution and functional capacity in growth period.ObJective: The aims of this research were to know the differences of body constitution, grip strength, and vital capacity of 15-18 year old children in Samigaluh highland and Galur lowland in Kulonprogo, Yogyakarta Province, and the relationship between body constitution, grip strength, and vital capacity of both populations. Methods: The research was done on 422 boys and girls of 1 5-18 years, which consisted of 152 children living in Samigaluh and 270 children living in Galur Kulonprogo. The children were examined with respect to body weight, height, grip strength of right and left hands, and vital capacity. Body Mass was Index then calculated from weight and height. Statistical analysis of three way ANOV A, t-test, Pearson product moment correlation, and linear regression were used.Results: Body constitution, grip strength, and vital capacity of boys differed significantly from girls. Boys were heavier and taller than girls. Grip strength and vital capacity were also greater in boys. Children living in Galur were heavier and taller than those living in Samigaluh, but they were similar in vital capacity. Grip strength was different at age of 15-16 years. There was no difference in Body Mass Index between boys and girls, as well as between Samigaluh children and Galur children.Conclusions: Body constitution, grip strength, and vital capacity of boys and girls were different significantly, also between Samigaluh and Galur children as well. Concerning Samigaluh children were shorter and lighter, it was said that Samigaluh children have better physical performance. Grip strength and vital capacity of 1 5 to 1 8 year old children living in Samigaluh highland and Galur lowland were stronger affected by body constitution than by age.Key words: body constitution; grip strength; vital capacity; 1 5-18 year old boys and girls